“The 15 Players' Tantrum”: Social Networks and Women's Football through the Documentary #SeAcabó: Diario de las campeonas - Dueñas Mohedas, Sonia; Martínez Pérez, Natalia; Cuenca Orellana, Nerea (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The non-consensual kiss between the former president of the RFEF, Luis Rubiales, and the footballer Jennifer Hermoso during the World Cup'23 triggered the #SeAcabó movement on social networks, thereby bringing to light the influence peddling and sexist practices hidden behind women's sport. The impact of these events was subsequently covered by both national and international media. From the perspective of cultural and gender studies, this article analyses the documentary #SeAcabó: Diario de las campeonas (Joanna Pardos, 2024) to study the obstacles and prejudices faced by women in the world of football during their professionalisation.